Theoretical studies of cation adsorption on hydroxylated a-A12O3 (corundum): electronic structure calculations - Yong C.W.; Warren M.C.; Vaughan D.J.; Hillier I.H. (My University, 2003)
The adsorption of alkali metal cations on a hydroxylated corundum surface was investigated using high-level electronic structure calculations, with both cluster Hartree–Fock and periodic density-functional theory approaches. The work concentrates on the structural aspects of binding sites with threefold oxygen coordination at the basal (0001) surface. It was found that adsorption at different sites can give rise to a wide range of adsorption energies, which strongly depends on the freedom of surface hydrogen atoms to adjust their positions. Alkali metal adions from Li+ to Cs+ were studied with the cluster method, periodic plane-wave pseudopotential calculations being carried out for K+ adsorption to validate the cluster results. A site above an octahedral interstice was found to be the least preferred for cation adsorption, despite having the lowest repulsion from surface aluminium atoms. The strongest adsorption was found over an aluminium atom in the second layer, because the hydroxyl groups could reorient towards the neighbouring octahedral interstices, and hence significantly decrease repulsion with the cation. The adsorption energy and the first three interlayer spacings parallel to the basal surface change systematically with ionic size for each adsorption site. Many of these trends extend to adsorption of Ca2+, Co2+ and Pb2+, which were also investigated, although a redistribution of 3d electrons in Co2+ results in strong adsorption even at an unfavourable site. The results suggest that it may be possible not only to predict adsorption behaviour for a wide range of elements, but also to use experimental measurements of interplanar separations to gain information about contaminated surfaces.
Keywords: corundum; a-A12O3